THE PHENOMENON OF EARLY-AGE SMOKING AMONG STUDENTS AT SMA NEGERI 7 GORONTALO - Sabbu, Aldi Bregi; Indriyanipoiyo, Indriyanipoiyo; Hikma, Hikma; Ramadhani, Vanya Dyah Pitaloka Maharani A.C. (PERSPEKTIF: Journal of Social and Library Science, 2025)
Early-age smoking remains a significant social issue among high school students. This study examines smoking behavior among students of SMA Negeri 7 Gorontalo, the factors influencing its emergence, and the effectiveness of social control within the family, school, and community. Using a descriptive qualitative approach, data were collected through observations, in-depth interviews, and documentation involving student smokers, peers, teachers, parents, and community members. The findings reveal that smoking is often carried out secretly and is primarily driven by peer influence, followed by smoking habits within the family, curiosity, easy access to cigarettes, and emotional pressure. Social control in schools and the community remains weak, contributing to the normalization of adolescent smoking. These results support Hirschi’s social control theory, which states that weakened social bonds increase the likelihood of deviant behavior. The study highlights the need to strengthen social control across all environments to reduce early-age smoking among students.